Pemanfaatan E-resources untuk Penelitian dan Publikasi Ilmiah - Cahyono, Teguh Yudi; Naningrum, Amma (Universitas Negeri Padang, 2024)
The utilization of e-resources has become an integral part of scientific research and publication, enabling researchers to access the latest and high-quality information across various fields of study. In this article, we conduct an in-depth analysis of the utilization of e-resources for scientific research and publication, focusing on various aspects including factors influencing usage, the most frequently used types of e-resources, challenges and solutions, as well as the implications of research findings. Our findings indicate that accessibility to information, fostering innovation, and supporting ethical research practices are some of the key benefits derived from the utilization of e-resources. Our recommendations for e-resource users include enhancing digital literacy, fostering collaboration among researchers, and evaluating information quality. The implications of our research findings demonstrate the significant contribution of e-resource utilization to enhancing the quality of scientific research and publication.